Across the Waves : How the United States and France Shaped the International Age of Radio - Vaillant, Derek (Book collections on Project MUSE., 2017)
"This book is the first comparative history of 20th-century U.S.-French radio broadcasting and its consequences for cultural politics and international/global communication. As U.S. electronics firms raced into Europe, a succession of French governments cautiously participated in U.S.-French broadcast experiments. The first "transatlantics" revealed disparate national visions of radio's place in the emerging international/global arena. During World War II, however, and continuing into the Cold War years, U.S.-French broadcasting and statecraft wove tightly together, with tangible consequences for how Americans and the French learned to listen to each other. Radio became a projection space of U.S.-French national identity and difference, shaping culture and politics in an international/global media age. This book studies the period from 1931--when live, two-way programs first linked Paris and New York--to 1974, when France disassembled its state media system and the curtain fell on almost a half century of close and continuing radio association. This book uses extensive research in U.S. and French archives to analyze the work of transnational cooperative enterprises, notably among them an initiative to bring a torrent of French-produced, English-language content onto U.S. airwaves after World War II. It shows how a mobile cohort of U.S. and French nationals and expatriates created radio's transnational/global technical structures and aesthetic possibilities, and analyzes how different aesthetic aims and technical systems shaped cultural politics between us. This book brings the history of radio squarely into scholarly conversations about the root formations and tendencies of contemporary global media"--